Hyaluronic acid as a promoter of the healing of post-extraction socket treated with the socket preservation technique: a systematic review - Pizzolante, Tommaso; Benincasa, Gianluca; Bizzarro, Francesco; Capogreco, Mario; Marchetti, Enrico (Frontiers in Oral Health, 2025)
BackgroundThis review examines the role of hyaluronic acid (HA) in enhancing the healing of the post-extraction socket. HA, a naturally occurring glycosaminoglycan in the extracellular matrix, is crucial for wound healing. It promotes tissue repair by stimulating cell migration, adhesion, and proliferation, essential for bone formation. When combined with deproteinized bovine bone mineral (DBBM), HA may improve bone regeneration and reduce resorption, though evidence is still limited.MethodsThree clinical studies were reviewed, assessing primary outcomes such as volumetric bone resorption, linear bone loss, and soft tissue healing. Radiographic evaluations, including cone beam computed tomography (CBCT), were used to quantify bone changes, while clinical assessments were conducted to evaluate soft tissue responses and wound healing over a 4-month follow-up period.ResultsTwo studies demonstrated that HA, in combination with DBBM, significantly improved bone preservation. These studies found reduced volumetric bone resorption and enhanced bone width retention, with one showing a significant reduction in crestal bone loss (p < 0.001). In contrast, the third study did not report any significant improvements in soft tissue healing or bone preservation with HA treatment.ConclusionsThe results of this review suggest that HA, combined with DBBM, may offer significant benefits in reducing bone resorption and preserving bone width in ARP procedures. However, the impact of HA on soft tissue healing cannot yet be statistically evaluated, highlighting the need for further investigation to optimize its use in clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024526628, PROSPERO CRD42024526628.